Erratum: An intrinsic mechanism controls reactivation of neural stem cells by spindle matrix proteins. Issue 1 (December 2017) - Li, Song; Koe, Chwee; Tay, Su; Tan, Angie; Zhang, Shenli; Zhang, Yingjie; Tan, Patrick; Sung, Wing-Kin; Wang, Hongyan
Abstract A correction to this article has been published and is linked from the HTML version of this article.